Correlating traditional harvest practices of roots of medicinal plant Hemidesmus indicus with therapeutic biomolecule levels: with reference to traditional inscriptions - Sreya Dutta
Traditional texts mention some specific guidelines for harvesting of medicinal plants based on the seasons. These ancient practices are grounded in centuries of empirical knowledge and observation, aiming to maximize the plant's medicinal efficacy and potency. In this light, the present study considered an important medicinal herb Hemidesmus indicus to quantify an active phytocompound lupeol present in the plant root collected in different seasons and variations in morphoanatomical and phytochemical assay. Flavonoid and phenolic contents were investigated as a phytochemical assay. To estimate the quantity of lupeol a reliable, precise, reproducible and validated HPLC method was conducted. The study revealed that the lupeol content is highest in winter season (0.4029%) while least in rainy season (0.2739%) and there were no significant differences in pharmacognostical characters, but phytochemical contents were noted with significant variations. The total phenolic contents were highest in spring days (8.34%) and total flavonoid contents are highest in summer season (4.16%). The significant outline of the present piece of work based on the lupeol content and concentration of other secondary metabolites assures the relevancy of ancient wisdom in contemporary times through prudent utilisation of natural resources and sustainable growth of mankind. This is because results obtained through the investigations ensure the seasonal preferences as stated in ancient texts. These findings help in bridging traditional knowledge with contemporary understanding, ensuring safe and effective utilization of medicinal plants.